Growth Suppression of a Gingivitis and Skin Pathogen Cutibacterium (Propionibacterium) acnes by Medicinal Plant Extracts - Hyoung-An Choi; Sang-Oh Ahn; Ho-Dong Lim; Geun-Joong Kim (MDPI AG, 2021)
Propionibacterium acnes, newly reclassified as Cutibacterium acnes, is an anaerobic Gram-positive bacterium causing acne, found mainly on the skin. In addition, P. acnes is responsible for inflammation of the gums (gingivitis) and blood vessels, consequently leading to various diseases in the human body. In recent years, the evolution of microorganisms, such as P. acnes, that have become resistant to many commercial antibiotics due to the widespread use of antimicrobial drugs in the treatment of infectious diseases has emerged as a major clinical problem. We here analyzed the potential use of 37 medicinal plant extracts as plausible candidates for treating P. acnes, in terms of total phenolic and flavonoid contents, antioxidants scavenging and antimicrobial activity. Consequently, methanol extracts from 14 medicinal plants showed promising antimicrobial activities against P. acnes. In particular, as the extracts from Chrysosplenium flagelliferum F. and Thuja orientalis L. exhibited distinct antimicrobial activities in both the broth dilution and disc diffusion assay, they could be effectively used as active ingredients for preventing or treating inflammatory periodontal diseases, such as periodontitis.